(untitled) (Altre Modernità, 2019)
Starting from Cronin’s study on the relationship between language and translation in tourism, this article explores the different degrees of cultural diversity through some examples of intralinguistic translation, use of foreign words in monolingual texts and interlingual translation between Spanish, English and Italian. In the perspective of accessibility, a dynamic model for the management of cultural diversity in tourism is proposed, based on the communicative needs of the tourist, which can include different modes of translation. In particular, the importance of two preliminary steps is stressed: the analysis of the discursive genre to which the texts belong and the selection of cultural information.